2009 Asia Pacific Microwave Conference 2009
DOI: 10.1109/apmc.2009.5385421
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of on-body channels with top-loaded monopole antennas in the range of HF to UHF

Abstract: In recent years, body-centric wireless communications have become an active area of research due to their various applications. Whereas UHF bands are subjects of interest especially in Europe, relatively low frequency bands below several megahertz are also in researchers' and corporations' interest especially in Japan. Thus, all of the candidate frequencies are in an extremely wide range. Our purpose is to bring objective and unified idea on the frequency characteristics of body-centric wireless communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…This paper presents a study of on-body channels during walking and comparison is made with other investigations, [1][2][3][4][5][6][7][8][9][10]. In [1][2][3][4] BAN studies were based on measurements on humans while [5] relied solely on EM simulations on a phantom.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper presents a study of on-body channels during walking and comparison is made with other investigations, [1][2][3][4][5][6][7][8][9][10]. In [1][2][3][4] BAN studies were based on measurements on humans while [5] relied solely on EM simulations on a phantom.…”
Section: Introductionmentioning
confidence: 99%
“…BAN channel variation during walking has been studied for a single model in [1], [2], [4][5][6][7][8] and for a population of models in [3], [9], [10]. While [9] showed that a population with similar height had comparable forward transmission (S 21 ) levels for a given walking stance, differences between individuals were not negligible and could be up to 10dB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antenna has low-profile dimension (4-mm thick) and has no matching structure for simplicity. [7].…”
Section: Wearable Dual-mode Antennamentioning
confidence: 99%